Genetic variation, diversity and molecular phylogenetic of higher group termite Macrotermes carbonarious Hagen (Blattodea: Termitidae) - Abdul Hafiz Ab Majid,; Eng, Yi Shen; Chong, Yeak Heng; Liew, Chin Foong (Penerbit Universiti Kebangsaan Malaysia, 2018)
Limited studies pertaining to evolutionary history and intraspecific diversity of Macrotermes genus have been carried out by researchers. Such studies are vital as from phylogeny we can understand the origin of species in a particular region. Thus, in this study, we investigated the phylogenetic relationships and genetic diversity among the population of Macrotermes carbonarius around USM campus. Seventeen Macrotermes carbonarius colonies were used to conduct a molecular genotyping study and the mitochondrial (COII) gene was used as marker. The data obtained were analyzed using T-Coffee, Clustal X, Mega 7.0 and DnaSP software programs. Our results show one main monophyletic clade that consists of two groups: HP1 and HP2. The samples from Stadium Hoki were classified in HP2, differing from the other populations studies by one singleton base. Our HP2 shows some similarity with some sequence from Pasoh Forest Reserved Malaysia, suggesting a state diversity connection. The disparity index suggests that all the samples are homogeneous populations, supported by the low value of mean pairwise distance between the samples. This study will serve as a platform for scientific community to enhance the knowledge on the phylogeny and genetic diversity of Macrotermes genus in South East Asia region.